2002
DOI: 10.1074/jbc.m201366200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Toll-like Receptor (TLR) 2 and TLR4 in Cell Activation by Mannuronic Acid Polymers

Abstract: The alginate capsule produced by the human pathogen Pseudomonas aeruginosa is composed mainly of mannuronic acid polymers (poly-M) that have immunostimulating properties. Poly-M shares with lipopolysaccharide the ability to stimulate cytokine production from human monocytes in a CD14-dependent manner. In the present study we examined the role of Toll-like receptor (TLR) 2 and TLR4 in responses to poly-M. Blocking antibodies to TLR2 and TLR4 partly inhibited tumor necrosis factor production induced by poly-M in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 179 publications
(108 citation statements)
references
References 46 publications
1
106
1
Order By: Relevance
“…We and others have previously shown that TLR4 [23,42] as well as TLR5 [24,43] is also involved. Differential engagement of PRR involved in P. aeruginosa recognition could depend on the site or the time of infection and the prevailing microbial ligand.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We and others have previously shown that TLR4 [23,42] as well as TLR5 [24,43] is also involved. Differential engagement of PRR involved in P. aeruginosa recognition could depend on the site or the time of infection and the prevailing microbial ligand.…”
Section: Discussionmentioning
confidence: 79%
“…TLR2 has been reported to participate in recognition of multiple P. aeruginosa ligands, including lipoproteins [23,51], alginate [42], flagellin [52], and exoenzyme S [21]. TLR2 is an endocytic receptor [53] and has been reported to recruit phagosomes containing yeasts specifically to macrophage [36].…”
Section: Discussionmentioning
confidence: 99%
“…Soluble alginate rich in mannuronic acid (>86%) is able to induce TNF in monocytes through mechanisms involving CD14 [30] TLR2 and TLR4 [31]. Recently it was demonstrated that purified alginate rich in guluronic acid as used currently, did not activate TLRs [32].…”
Section: Cd11b Cd18 or Cd11c Blockagementioning
confidence: 99%
“…The preparation was characterized by quantitative PCR for the single copy wsp gene (29) and by immunofluorescent staining and counting on a FACSVantage flow cytometer (BD Biosciences). (30,31). The cells were maintained in DMEM (Cellgro) supplemented with 10% low endotoxin FCS (Atlanta Biologicals) in a 5% saturated CO 2 atmosphere at 37°C.…”
Section: Isolated Wolbachia Bacteriamentioning
confidence: 99%